Proinflammatory microglial response is a common mechanism of Aroclor 1254- and Tetrabromobisphenol-A-induced neurotoxicity in immature chronically exposed rats - Dąbrowska-Bouta, Beata; Sulkowski, Grzegorz; Frontczak-Baniewicz, Małgorzata; Sulejczak, Dorota; Strużyńska, Lidia (Folia Neuropathologica, 2024)
Polychlorinated biphenyls (PCBs) and brominated flame retardants (BFRs) are dominant environmental and food contaminants. Tetrabromobisphenol A (TBBPA) is the most widely used BFR in the world to improve the fire safety of laminates in electrical and electronic equipment. Aroclor 1254, one of the PCBs, is widely distributed in the environment due to its extensive use in industrial applications around the world. Both groups of substances are potent toxicants. There is also increasing evidence that they have neurotoxic effects. In this study we tested the pro-inflammatory effects of Aroclor 1254 and TBBPA based on markers of microglial reactivity and levels of pro-inflammatory factors in the brain of immature rats. Aroclor 1254 or TBBPA were administered to the rats by oral gavage for two weeks at a dose of 10 mg/kg b.w. Both light and electron microscopy studies revealed features indicative of microglia activation in brains of exposed rats. Morphological changes were associated with overexpression of pro-inflammatory enzymes such as inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). Analysis of cytokine/chemokine array revealed significant secretion of inflammatory mediators following exposure to both TBBPA and Aroclor 1254, which was stronger in the cerebellum than in the forebrain of exposed immature rats. The results indicate a pro-inflammatory profile of microglia activation as one of the neurotoxic mechanisms of both examined toxicants.